2010
DOI: 10.1007/s10072-010-0344-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of natalizumab in relapsing–remitting multiple sclerosis patients: a post-marketing observational study

Abstract: To evaluate the efficacy and safety of natalizumab in patients with active relapsing-remitting multiple sclerosis (MS). We included 285 MS patients receiving natalizumab. Clinical, neuroradiological and safety data were registered every 6 months. Neutralizing antibodies (NABs) were tested after 6 months of treatment. After 1 year, the annualized relapse rate decreased to 0.26, with a significant reduction compared to the previous year (2.13). At 24 months the proportion of "relapse free" patients was 78% while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
24
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 3 publications
12
24
2
2
Order By: Relevance
“…In general, our results fit those earlier reported in other post-marketing studies, regarding efficacy and safety. [5][6][7][8][9][10][11] Our data are also consistent with previous findings in terms of baseline patients' profile: age at NZ starting, ARR in the year prior to NZ and clinical MS form. [5][6][7][8][9][10][11] Exception for consistency with other previous findings is made for baseline EDSS and disease duration until NZ, both found to be higher in our study than others 'real-world' studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In general, our results fit those earlier reported in other post-marketing studies, regarding efficacy and safety. [5][6][7][8][9][10][11] Our data are also consistent with previous findings in terms of baseline patients' profile: age at NZ starting, ARR in the year prior to NZ and clinical MS form. [5][6][7][8][9][10][11] Exception for consistency with other previous findings is made for baseline EDSS and disease duration until NZ, both found to be higher in our study than others 'real-world' studies.…”
Section: Discussionsupporting
confidence: 92%
“…[5][6][7][8][9][10][11] Our data are also consistent with previous findings in terms of baseline patients' profile: age at NZ starting, ARR in the year prior to NZ and clinical MS form. [5][6][7][8][9][10][11] Exception for consistency with other previous findings is made for baseline EDSS and disease duration until NZ, both found to be higher in our study than others 'real-world' studies. [5][6][7][8][9][10][11] It's possible that patients were included too late in the disease evolution; it may be explained by some initial reluctance in NZ prescription, regarding safety concerns, namely PML.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Following the development of a risk management strategy, the drug was reintroduced into the marketplace in June 2006. Since that time, the postmarketing experience has substantiated the impressive efficacy of natalizumab, but also confirmed the ability of this agent to increase the development of PML in a small percentage of patients [Sangalli et al 2011;Kappos et al 2011;Biogen Idec, 2011]. The dynamics of the JC virus infection, the host immune response (the presence of JC virus IgG appears to portend a higher risk of PML than patients who are seronegative), and the influence of antecedent treatments (e.g.…”
Section: A Change In Treatment Strategymentioning
confidence: 89%
“…A subsequent post-hoc analysis introduced the concept of freedom from disease and showed that 37% of patients included in the AFFIRM study remained free of both clinical activity and radiological activity at 2 years [3,4]. Since then, several post-marketing studies have confirmed the effectiveness of NTZ in daily clinical practice [5,6,7,8,9,10,11], although only a few have exclusively evaluated the effectiveness of NTZ in patients with highly active RRMS (HA-RRMS) [12,13]. …”
Section: Introductionmentioning
confidence: 99%